Filling in the blanks: How does information about the Swedish EITC affect labour supply? - Pär Nyman; Linuz Aggeborn; Rafael Ahlskog (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
Information plays a key role in economics. According to the benchmark neoclassical model, agents require information in order to optimize their choices. Information, however, is sometimes incomplete or asymmetric in the real world. In this paper, we investigate the role of information for the labour-leisure choice. We conduct an information experiment wherein we distribute a leaflet about the Swedish Earned Income Tax Credit (EITC), and then study the effects with registry data. More specifically, we focus on the household decision to allocate between labour income and parental leave payments. The EITC, it bears noting, applies to the former but not to the latter. The construction of the Swedish EITC generates a strong economic incentive to have some labour income during a calendar year, because it is tailored to benefit low labour income earners more in relative terms. Yet, despite the substantial economic incentives involved, and despite the flexibility with which a person may earn labour income, we find that providing information about the features of the EITC has zero impact on labour supply
Keywords: J18; I21; I26; 330; Labour Supply; Information; Experiment; Earned Income Tax Credit; Sweden